Contamination routes and mortality of the leaf-cutting ant Atta sexdens (Hymenoptera: Formicidae) by the insecticides fipronil and sulfluramid through social interactions - Mota Filho, Tarcísio M M [UNESP]; Camargo, Roberto S [UNESP]; Zanuncio, José C; Stefanelli, Luis E P [UNESP]; de Matos, Carlos A O [UNESP]; Forti, Luiz C [UNESP] (Wiley, 2021)
BACKGROUND: Leaf-cutting ants (LCAs) of the genera Atta and Acromyrmex (Hymenoptera: Formicidae) are important pests of forest plantations, agriculture and livestock. Toxic baits containing the active ingredients fipronil or sulfluramid are the main method used to control LCAs. Insecticide dispersion among members of an LCA colony during control with toxic bait is not well understood. The objective of the study was to determine whether self-grooming, allogrooming or touching behavior among Atta sexdens (Hymenoptera: Formicidae) workers disperses the insecticides fipronil and sulfluramid among members of the colony. The insecticides were topically applied on groups of A. sexdens workers and social interactions between ants with and without insecticide, and group mortality were evaluated. RESULTS: Behavioral analysis showed an increase in interaction among LCA workers as the numbers of individuals increased, with touches between workers being the most frequent behavior. The frequency of observed behaviors was higher in groups treated with sulfluramid compared with fipronil. The mortality of groups treated with fipronil was almost twice as high compared with ants treated with sulfluramid. The insecticides are probably dispersed by excessive touching among workers and subsequent self-grooming and allogrooming. CONCLUSION: These behaviors were responsible for the rapid dispersion of insecticides among members of the colony. Corroboration of the hypothesis that social interactions contaminate nestmates is a model for future studies on contamination of ant workers with active insecticide ingredients.
Keywords: Atta; insecticides; social interactions; trophallaxis